2022
DOI: 10.1001/jamaneurol.2022.2379
|View full text |Cite
|
Sign up to set email alerts
|

Association of Elevated Amyloid and Tau Positron Emission Tomography Signal With Near-Term Development of Alzheimer Disease Symptoms in Older Adults Without Cognitive Impairment

Abstract: ImportanceNational Institute on Aging–Alzheimer’s Association (NIA-AA) workgroups have proposed biological research criteria intended to identify individuals with preclinical Alzheimer disease (AD).ObjectiveTo assess the clinical value of these biological criteria to identify older individuals without cognitive impairment who are at near-term risk of developing symptomatic AD.Design, Setting, and ParticipantsThis longitudinal cohort study used data from 4 independent population-based cohorts (PREVENT-AD, HABS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…It is likely that other non-amyloid factors have a similar impact on disease progression, accelerating progression in some Aβ+ individuals but allowing for resilience to downstream changes in other Aβ+ individuals [56]. Given the link between elevated tau burden and risk of clinical progression from CU to MCI [14], the identification of factors that influence tau burden among Aβ+s will improve individual level prediction and shed insight into mechanisms of disease risk and resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that other non-amyloid factors have a similar impact on disease progression, accelerating progression in some Aβ+ individuals but allowing for resilience to downstream changes in other Aβ+ individuals [56]. Given the link between elevated tau burden and risk of clinical progression from CU to MCI [14], the identification of factors that influence tau burden among Aβ+s will improve individual level prediction and shed insight into mechanisms of disease risk and resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Tau abnormalities are a stronger predictor of concurrent cognitive ability and future cognitive impairment than Aβ status alone [12][13][14]. Although both amyloid and tau abnormalities are strongly related such that elevated tau is very uncommon among Aβ-individuals, there is substantial variability in the magnitude of tau PET uptake within Aβ+ individuals [12,[15][16][17][18][19][20], highlighting that additional factors beyond amyloid contribute to downstream tau accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of Aβ plaques and regional tau tangles were modeled separately to distinguish their respective contributions in the downstream tau accumulation. Furthermore, many studies reported that abnormal tau tangles outside the entorhinal cortex were rarely observed in the absence of substantial cortical Aβ burden [9,20,21,25,42], and larger Aβ burden was strongly related to more rapid tau accumulation over time [5,10,11,20]. Altogether, it might be possible that the existing tau tangles contribute more to longitudinal tau accumulations in late tau-deposited ROIs of temporal meta-ROI than cortical Aβ plaques when Aβ plaques and tau tangles are already widespread in neocortex and temporal meta-ROI.…”
Section: Discussionmentioning
confidence: 99%
“…10 Given this information, the ability to measure tau burden in living persons is crucial in establishing an accurate diagnosis of Alzheimer’s disease and predicting one’s risk towards clinical progression. 25 …”
Section: Discussionmentioning
confidence: 99%